Clinical Evaluation of Right Orbital Cellulitis in An Elderly Patient - Lulu Naeluvar; Kantika Prinandita; Meriana Rasyid (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Orbital cellulitis is a severe infection of the intraorbital tissues that can threaten vision and requires prompt management. This study aims to describe the clinical characteristics, diagnosis, and management of orbital cellulitis in an elderly patient with systemic risk factors. A descriptive clinical approach was employed, collecting data through anamnesis, physical examination, and ophthalmologic assessments including visual acuity, slit-lamp examination, and fundus evaluation, as well as the patient’s medical and treatment history. Data were analyzed qualitatively to illustrate the clinical manifestations, diagnosis, and therapeutic interventions. The case involved a 64-year-old male presenting with redness, swelling, pain, tearing, and difficulty opening the right eye for one week, with a history of diabetes mellitus and dental caries. Physical examination revealed palpebral edema, conjunctival and scleral hyperemia, restricted ocular motility, and decreased visual acuity in the right eye. The definitive diagnosis was orbital cellulitis in the right eye, with cataract in the left eye and diabetes mellitus as comorbidities. Management included broad-spectrum topical antibiotics and referral to both ophthalmology and internal medicine specialists for multidisciplinary care. In conclusion, early intervention and accurate clinical diagnosis are essential to prevent severe complications such as subperiosteal abscess, cavernous sinus thrombosis, or permanent vision loss.